When Food Meets Man: the Contribution of Epigenetics to Health - Fabiani, Emma De (MDPI, 2010)
Post-translational modifications of chromatin contribute to the epigenetic control of gene transcription. The response to food intake and individual nutrients also includes epigenetic events. Bile acids are necessary for lipid digestion and absorption, and more recently have emerged as signaling molecules. Their synthesis is transcriptionally regulated also in relation to the fasted-to-fed cycle, and interestingly, the underlying mechanisms include chromatin remodeling at promoters of key genes involved in their metabolism. Several compounds present in nutrients affect gene transcription through epigenetic mechanisms and recent studies demonstrate that, beyond the well known anti-cancer properties, they beneficially affect energy metabolism.